A Study on the Differences in Rumen Microbiota–Liver Gluconeogenesis–Mitochondrial Interaction Between Tibetan Sheep and Hu Sheep in the Qinghai–Tibet Plateau - Qianling Chen; Yuzhu Sha; Xiu Liu; Min Gao; Xiaowei Chen; Wenxin Yang; Wei Huang; Jiqing Wang; Yapeng He; Xu Gao; Yanyu He (Animals)
As high-quality sheep germplasm resources in China, Hu sheep are characterized by fast growth and development, high fecundity, and tolerance to drought and cold. Tibetan sheep, adapted to high-altitude environments, have developed strong environmental adaptability. To explore the differences in the interaction among rumen microbial flora, hepatic gluconeogenesis, and mitochondrial function between Tibetan sheep and Hu sheep in the Qinghai–Tibet Plateau, this study systematically compared and analyzed the rumen flora density, key enzyme activities related to hepatic gluconeogenesis and mitochondrial function, and the expression levels of related genes in Tibetan sheep and Hu sheep under identical feeding management conditions, followed by correlation analysis. The results showed that Hu sheep had significantly higher densities of Ruminobacteramylophilus (Ram) and Fibrobacter succinogenes (Fs) associated with starch and protein degradation (p < 0.01). The expression levels of Forkhead box O1 (FOXO1), pyruvate carboxylase (PC) activity, and adenosine triphosphate (ATP) content were also significantly higher than those in Tibetan sheep (p < 0.01). In contrast, Tibetan sheep had higher densities of Butyrivibrio fibrisolvens (Bf), Ruminococcus albus (Ra), Ruminococcus flavefaciens (Rf), etc., related to cellulose degradation (p < 0.01). The gluconeogenesis-related genes, Glucose-6-phosphatase catalytic subunit 1 (G6PC1) and phosphoenolpyruvate carboxykinase1 (PCK1), and the activities of phosphoenolpyruvate carboxykinase (PEPCK) and fructose-1,6-bisphosphatase (FBPase) were significantly higher in Tibetan sheep than in Hu sheep (p < 0.01). Mitochondrial function-related genes Mitofusin-1 (Mfn1), Mitofusin-2 (Mfn2), subunit 6 of ATP synthase (ATP6), cytochrome b (Cytb), etc., also showed significantly higher expression in Tibetan sheep (p < 0.01). While no significant differences were observed in the contents of citric acid (CA), pyruvic acid (PA), glucose (Glu), etc. (p > 0.05). Correlation analysis indicated that rumen flora was associated with the key enzyme activities and gene expressions of hepatic gluconeogenesis and mitochondrial function to varying degrees. In summary, Tibetan sheep exhibit strong fiber degradation capacity, the efficient utilization of gluconeogenic intermediates, and mitochondrial oxidative phosphorylation (OXPHOS) ability, forming adaptive strategies for high-altitude environments. By contrast, Hu sheep show efficient protein and starch degradation capacity, thereby enhancing the supply of gluconeogenic precursors. It is indicated that when introducing Hu sheep to high-altitude areas, dietary intervention can be used to regulate rumen microorganisms, such as increasing fiber-decomposing bacteria or enhancing mitochondrial oxidative capacity, to counteract metabolic limitations induced by hypoxia.